Falls, perceived fall risk and activity curtailment among older people receiving home-help service - Vikman, Irene (Luleå tekniska universitet, Hälsa och rehabilitering, 2011)
Falls and fall-related concern and fear of falling are not well understood when it comes to old people receiving home-help services, a transitional population in-between those living independently in the community and those living in residential care facilities. The psychological distress attributable to the perceived risk of falling among this population needs further exploration, which is also the case regarding possible ways to increase their feeling of security. The aims of this thesis were to investigate the incidence of falls, fall-related concern, fear of falling and fall-related activity curtailment amongst older people receiving homehelp services, as well as exploring the validity and user expectations of an automatic fall detector and alarm prototype. In a one-year prospective cohort study of 614 home-help recipients in one municipality in northern Sweden, the fall incidence was estimated to be 626 (95% CI: 479 – 773) per 1,000 person-years. The fall risk was significantly associated with receiving help for personal ADL needs: IRR 2.8 (95 % CI: 2.1 - 3.8). An unexpected finding was that the fall incidence was significantly correlated to the amount of daylight (r: -0.78, r2: 0.61; p: 0.003). A cross-sectional study of 51 home-help recipients in three municipalities in northern Sweden revealed that 65% (95% CI: 52% – 78%) had a high degree of concern about falling according to the Falls Efficacy Scale International (FES-I). This concern was significantly associated with concern about the consequences of falling, mobility and morale, but its correlation to fear of falling was moderate. The proportion reporting that they needed assistance to perform a specific activity or avoided one owing to a fear of falling was 57% and 26%, respectively. Such fear-dependent need for assistance was associated with morale and mobility, and fear-dependent activity avoidance with morale and fallrelated concern. While wearing a fall sensor attached to their hips, twenty middle-aged people performed six different intentional ...